Entrapment Neuropathy: A Concept for Pathogenesis and Treatment of Headaches—A Narrative Review. Issue 12 (March 2019) - de Ru, J Alexander; Filipovic, Boris; Lans, Jonathan; van der Veen, Erwin L; Lohuis, Peter JFM
Entrapment neuropathy is a known cause of neurological disorders. In the head and neck area, this pathophysiological mechanism could be a trigger for headache. Over the last few decades, injection of botulinum toxin type A in the muscles that are causing the compression as well as surgical decompression have proved to be effective treatment methods worldwide for large numbers of patients with daily headaches. In particular the entrapment of the supraorbital nerves in the glabellar musculature and the occipital nerves in the neck musculature are triggers for headache disorders for which many patients are still seeking an effective treatment. This article reviews the literature and aims to bring the concept of neural entrapment to the attention of a wider audience. By doing so, we hope to give more exposure to an effective and relatively safe headache treatment.